An informatics research agenda to support patient and family empowerment and engagement in care and recovery during and after hospitalization. (17th June 2017) - Collins, Sarah; Dykes, Patricia; Bates, David W; Couture, Brittany; Rozenblum, Ronen; Prey, Jennifer; O'Reilly, Kristin; Bourie, Patricia Q; Dwyer, Cindy; Greysen, S Ryan; Smith, Jeffery; Gropper, Michael; et al.
Abstract: As part of an interdisciplinary acute care patient portal task force with members from 10 academic medical centers and professional organizations, we held a national workshop with 71 attendees representing over 30 health systems, professional organizations, and technology companies. Our consensus approach identified 7 key sociotechnical and evaluation research focus areas related to the consumption and capture of information from patients, care partners (eg, family, friends), and clinicians through portals in the acute and post-acute care settings. The 7 research areas were: (1) standards, (2) privacy and security, (3) user-centered design, (4) implementation, (5) data and content, (6) clinical decision support, and (7) measurement. Patient portals are not yet in routine use in the acute and post-acute setting, and research focused on the identified domains should increase the likelihood that they will deliver benefit, especially as there are differences between needs in acute and post-acute care compared to the ambulatory setting.